Analysis of DICER1 in familial and sporadic cases of transposition of the great arteries. (5th February 2018) - Sabbaghian, Nelly; Digilio, Maria C.; Blue, Gillian M.; Revil, Timothée; Winlaw, David S.; Foulkes, William D.
Abstract: Objective: We previously identified a pathogenic germline DICER1 variant in a child with transposition of the great arteries who was a member of a family with DICER1 syndrome. In view of a report linking Dicer1 knockout in murine cardiomyocytes to cardiac outflow defects, we investigated the involvement of DICER1 in transposition of the great arteries. Design: We used Fluidigm access array followed by next generation sequencing to screen for variants in the coding exons, their exon/intron boundaries and the 3′ untranslated region of DICER1 in patient DNA. Cases: Germline DNA was collected from 129 patients with either sporadic or familial forms of transposition of the great arteries from two sites in Australia and Italy. Results: Most cases (85%) did not have any germline DICER1 variants. In the remaining 15% of cases, we identified 16 previously reported variants (5 synonymous, 6 intronic, and 5 missense) and 2 novel variants (1 intronic and 1 missense). None of the identified variants were predicted to be pathogenic. Conclusions: Here, we report that neither likely pathogenic nor pathogenic variants in DICER1 appear to play a major role in transposition of the great arteries.